EVALUASI EFEKTIVITAS PENERIMAAN PAJAK KENDARAAN BERMOTOR SEBAGAI SUMBER PENDAPATAN ASLI DAERAH TAHUN 2010-2014 PROVINSI JAWA TENGAH - Puspaningtyas Dyah Pramesthi; Turtiantoro .; Muhammad Adnan (Journal of Politic and Government Studies, 2015)
ABSTRACTTax is one of the government income that is very important for the government to function, especially as a stabilizer economy through budget policy to know up or decline in the economic growth of an area. A source of revenue among other local taxes and levies which is expected to be a source of income and as the largest funding source of governance, regional development, community and prosper. One source of revenue from taxes the province is the motor motor vehicle tax, in Central Java the motor vehicles tax enough to make contributions to a large local revenue. The government the ability of central java province in realizing the motor vehicles tax planned compared with a target collection based on the potential of motor vehicle tax describe the effectiveness of tax collection of motor vehicles. This research elaborated with the qualitative method that will produce data descriptive, the purpose of this research is to know the effectiveness of tax revenue of motor vehicles as a source of revenue Central Java province. Researchers used a technique purpose of sampling to do an interview with the head of tax and bbn-kb and employees of tax collector. The result of research shows motor vehicle tax revenue in Central Java is effective from the perspective of the revenue collected, this is proven by the percentage of tax revenue has reached more than one hundred percent, in other words revenue enough to fulfill the target. But in the process is not effective, because there are still some obstacles such as the level of community external economic support, community awareness remain low, the number of motor vehicle stealing case, the implementation of the low cost of green car and the absence of the increase in motor motor vehicle object in Central Java .Keywords : effectiveness, source of revenue, motor vehicle tax.